2017
DOI: 10.1002/suco.201700011
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of debonding mechanisms in carbon fiber reinforced polymer‐strengthened reinforced concrete continuous beams

Abstract: This paper presents three‐dimensional (3D) and two‐dimensional (2D) finite element models to analyze strengthened reinforced concrete (RC) continuous beams with carbon fiber reinforced polymer (CFRP) which has become familiar technique in the last decade. Experimental results in the literature showed that two different debonding failure modes, either by interfacial debonding of fiber reinforced polymer (FRP) or by concrete cover separation may occur. This study takes the two possible debonding failure modes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…To the authors' best knowledge most of researchers who studied strengthening of RC beams using UHPFRC material numerically assumed perfect bond between RC beam surface and UHPFRC layers or plates which neglect the slippage between concrete and UHPFRC and cannot capture the debonding failure mode. Herein, the cohesive surface model proposed by Sakr was used to model the adhesive surface behavior, in the following section there is a brief discussion explaining the cohesive surface model.…”
Section: Numerical Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…To the authors' best knowledge most of researchers who studied strengthening of RC beams using UHPFRC material numerically assumed perfect bond between RC beam surface and UHPFRC layers or plates which neglect the slippage between concrete and UHPFRC and cannot capture the debonding failure mode. Herein, the cohesive surface model proposed by Sakr was used to model the adhesive surface behavior, in the following section there is a brief discussion explaining the cohesive surface model.…”
Section: Numerical Investigationmentioning
confidence: 99%
“…A lot more researchers in the last decade studied, experimentally and numerically, the effectiveness of using carbon fiber reinforced polymer (CFRP) as a strengthening material . They concluded that the use of CFRP plates/sheets to strengthen RC beams was effective for reducing deflections and for increasing their load carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many unanchored U‐shaped CFRP beams, the actual failure mechanism is governed by sequential debonding, starting from the most vulnerable strip and continuing by propagation of critical diagonal shear cracking combined with the shear fracture of the beam in other strips . The occurrence of preliminary debonding of the FRP strips does not imply that the beam is not able to survive against existing load effects .…”
Section: Formulation Of Problemmentioning
confidence: 99%
“…In many unanchored U-shaped CFRP beams, the actual failure mechanism is governed by sequential debonding, starting from the most vulnerable strip and continuing by propagation of critical diagonal shear cracking combined with the shear fracture of the beam in other strips. 27,54 The occurrence of preliminary debonding of the FRP strips does not imply that the beam is not able to survive against existing load effects. 55 It is important to note that even the occurrence of preliminary debonding may impose a direct adverse effect on the serviceability, durability and subsequently load-carrying capacity of the beam, especially when the strengthened beam is exposed to wetting and drying cycles near seawater (extremely corrosive and Highly degradable, i.e., EH condition) over the longterm operation.…”
Section: Serviceability Limit Statementioning
confidence: 99%